2013
DOI: 10.1073/pnas.1217024110
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of cell cycle regulation triggers plant immune response via activation of disease resistance genes

Abstract: The Arabidopsis gene OSD1 (Omission of the Second Division) and its homolog UVI4 (UV-B-Insensitive 4) are negative regulators of anaphase-promoting complex/cyclosome (APC/C), a multisubunit ubiquitin E3 ligase that regulates the progression of cell cycles. Here we report the isolation of an activation tagging allele of OSD1 as an enhancer of a mutant of BON1 (BONZAI1), a negative regulator of plant immunity. Overexpression of OSD1 and UVI4 each leads to enhanced immunity to a bacterial pathogen, which is assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 47 publications
0
59
0
Order By: Relevance
“…RIG-I itself initially was identified as a protein involved in cell proliferation and differentiation (17). Many studies indicated that there were cross-talks between cell cycle regulation and immune response (18,19). To identify the novel proteins involved in the regulation of RIG-Imediated immune signaling as well as the cell cycle pathway, we screened a set of protein kinases that play important roles in the control of cell cycle using an IFN-b luciferase reporter assay.…”
Section: Resultsmentioning
confidence: 99%
“…RIG-I itself initially was identified as a protein involved in cell proliferation and differentiation (17). Many studies indicated that there were cross-talks between cell cycle regulation and immune response (18,19). To identify the novel proteins involved in the regulation of RIG-Imediated immune signaling as well as the cell cycle pathway, we screened a set of protein kinases that play important roles in the control of cell cycle using an IFN-b luciferase reporter assay.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that this reflects the reduced activation of cell division and, consequently, limited tumor expansion in the mutant-infected leaves. Recent work by Bao et al (2013) found an unexpected link between cell cycle progression and plant immunity, suggesting that cell cycle misregulation impacts the expression of R genes. Also, DNA repair proteins have been shown to be directly involved in the regulation of gene expression during plant defense responses (Song et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cell wall synthesis inhibition triggers pathogen response pathways and inhibits cell division and expansion (Hamann, 2015). Disturbance of the cell cycle is also known to trigger pathogen responses (Bao et al, 2013). Cell wall synthesis CSDL mutants, warty and slender leaf, have overlapping phenotypes with nod-1, including reduced organ size, defects in cell division, and abnormal stomata differentiation (Hunter et al, 2012;Yoshikawa et al, 2013).…”
Section: Discussionmentioning
confidence: 99%